2021
DOI: 10.1039/d0cc06513g
|View full text |Cite
|
Sign up to set email alerts
|

A CoV2O4 precatalyst for the oxygen evolution reaction: highlighting the importance of postmortem electrocatalyst characterization

Abstract: Postmortem analysis of a CoV2O4 catalyst for oxygen evolution reveals the active species is likely a vanadium-free amorphous cobalt oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is also important to confirm whether the catalyst structure and composition are maintained after electrochemical AOR experiments. , To this end, we conducted postmortem materials characterization on the Co 2 NiO 4 catalysts after subjecting electrocatalytic films to rotating disk electrode controlled potential electrolysis (RDE-CPE) measurements under catalytically relevant conditions: mounted into a rotating disk electrode (RDE) assembly at 1600 rpm rotation rate and held at 1.55 V vs RHE in 0.1 M NaOH electrolyte with 0.10 M n -BuOH. A representative RDE-CPE experiment under these conditions is shown in Figure S6 and shows an ∼25% decrease in activity over the 2 h electrolysis consistent with the activity losses seen for various analogously prepared catalyst films studied for the OER. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also important to confirm whether the catalyst structure and composition are maintained after electrochemical AOR experiments. , To this end, we conducted postmortem materials characterization on the Co 2 NiO 4 catalysts after subjecting electrocatalytic films to rotating disk electrode controlled potential electrolysis (RDE-CPE) measurements under catalytically relevant conditions: mounted into a rotating disk electrode (RDE) assembly at 1600 rpm rotation rate and held at 1.55 V vs RHE in 0.1 M NaOH electrolyte with 0.10 M n -BuOH. A representative RDE-CPE experiment under these conditions is shown in Figure S6 and shows an ∼25% decrease in activity over the 2 h electrolysis consistent with the activity losses seen for various analogously prepared catalyst films studied for the OER. ,, …”
Section: Resultsmentioning
confidence: 99%
“…For postmortem PXRD and ICP-MS measurements, particles were collected from the electrode surface using a previously reported procedure . Briefly, each modified working electrode was removed from the electrolyte and RDE sheath after the unsealed CPE measurements and submerged in i -PrOH in a centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding not only revealed the catalytic activity of CoV-MOF-derived annealed materials but also showed that it is necessary to conduct postmortem analysis of the catalyst after electrocatalysis to know the fate of the starting material. 36–38…”
Section: Introductionmentioning
confidence: 99%